COMPARISON OF MICROBIOTA IN THREATENED PRETERM LABOR AND NORMAL PREGNANCY AT RSUP DR.M. DJAMIL PADANG - Muhammad Ryfki SA; Roza Sri Yanti; Bobby Indra Utama (Universitas Andalas, 2024)
One of the threats in pregnancy is threatened preterm labor. Several studies show that thecomposition of the microbiota in the vagina of premature births and normal pregnancies is different.This study aims to determine the comparison of microbiota in pregnancies with premature parturitionand normal pregnancies at Dr M Djamil General Hospital, Padang. This research is an analyticalobservational study with a case–control study design conducted at the Department/SMF of Obstetricsand Gynecology, RSUP Dr. M. Djamil Padang from July – September 2023. The study population in thisresearch were all pregnant women with a gestational age of 20-37 weeks who were diagnosed withimminens preterm labor and normal pregnant women with a gestational age of 20-37 weeks whoreceived antenatal care at RSUP Dr. M. Djamil Padang. Respondents had vaginal swabs taken formicrobiological culture at the Biomedical Laboratory, Andalas University, Padang. There were 33respondents each in the imminence premature birth and normal pregnancy groups. Vaginal swabresults showed that the most common microorganism found in normal pregnancy was Lactobacilussp. (73%) while in threatened preterm labor Staphylococcus aureus (37%), Staphylococcus epidermidis(27%) and E.coli (15%) were more commonly found with only a small proportion of Lactobacilus sp(12%). Chi square analysis showed a significant difference between the vaginal microbiota of normalpregnant women and pregnant women with PPI. The conclusion of this study is that there is anincrease in Staphylococcus aureus, Staphylococcus epidermidis and E.coli in pregnant women on PPIwith a decrease in the number of normal flora, namely Lactobacilus spp.